Studi Pengaruh Variasi Elektroda SMAW Terhadap Sifat Mekanis Sambungan Las Dissimilar Baja Karbon St60 dan Stainless Steel Aisi 304 - M Ilham Nur; Muhammad Arham; Ramli Ramli; Risa B Umar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This research investigates the effect of electrode type on the mechanical properties of welded joints between ST60 carbon steel and AISI 304 stainless steel using the Shielded Metal Arc Welding (SMAW) method. The study involved tensile and hardness tests on base materials and welded joint regions. Tensile test results show that AISI 304 stainless steel in its initial condition has a maximum tensile strength of 664.27 MPa, while unwelded ST60 steel exhibits the same value. For welded joint specimens, the E6013 electrode produced a maximum tensile strength of 514.06 MPa, which is lower than that obtained using the E308-16 electrode at 560.52 MPa. These results indicate that the E308-16 electrode provides better tensile performance in welded joints. Hardness test results show that ST60 steel has an average hardness of 57 N/mm², while AISI 304 stainless steel has an average hardness of 63.1 N/mm². In welded joints using the E6013 electrode, the highest hardness occurs in the weld metal region, with an average of 66.3 N/mm². In contrast, welded joints produced using the E308-16 electrode show lower hardness in the weld metal region than the base materials. Overall, electrode type significantly affects tensile strength and hardness distribution of welded joints.